The Sky Painter : Louis Fuertes, Bird Artist - Engle, Margarita; Bereghici, Aliona (New York : Two Lions, 2015)
Louis loves to watch birds. He takes care of injured birds and studies how they look and how they move. His father wants him to become an engineer, but Louis dreams of being a bird artist. To achieve this dream, he must practice, practice, practice. He learns from the art of John James Audubon. But as Louis grows up, he begins to draw and paint living, flying birds in their natural habitats.
Keywords: Fuertes, Louis Agassiz, -- 1874-1927 -- Juvenile poetry; Fuertes, Louis Agassiz, -- 1874-1927 -- Poetry; Animal painters -- Juvenile poetry -- United States; Children's poetry, American; Animal painters -- Poetry; American poetry